Institutional Pressure and Green Product Success: The Role of Green Transformational Leadership, Green Innovation, and Green Brand Image - Zhou, Jian; Sawyer, Lucinda; Safi, Adnan (Frontiers in Psychology, 2021)
Rapid economic growth has led to economic activities which have caused extensive environmental damage to the planet. Companies have sought to adapt their business methods to reduce their carbon footprint in order to meet regulations, satisfy consumer preferences and keep up with changing societal expectations. The relationship between institutional pressure and green product performance will be an important issue in corporate green management. This article looked through the lens of green innovation and explored the moderating role of green brand image between green product innovation and new green product success. Utilizing the data of 243 managers in Mainland China, structural equation modelling results found that institutional pressure is positively correlated to green transformational leadership, green transformational leadership is positively correlated to green process innovation, green process innovation is positively correlated to green product innovation, green product innovation is positively correlated with new green product success, green brand image moderates the relationship between green product innovation and new green product performance. The research results provide theoretical and practical implications for enterprises to relieve institutional pressure and build specific green competitive advantages.